Vocalizações de Hyla werneri (Anura, Hylidae) no sul do Brasil - Lingnau, Rodrigo; Guimarães, Lorena D.; Bastos, Rogério P. (Phyllomedusa: Journal of Herpetology, 2004)
Herein, we describe the vocal repertoire of Hyla werneri. We found four distinct vocalizations: advertisement call, aggressive call, distress call, and a mixed call. The advertisement call was the most frequent vocalization, with one to 23 notes. Aggressive calls had only one note, but with longer duration than notes of advertisement calls. One individual emitted four distress calls, and these showed a great variation. The mixed calls are formed by the emission of an aggressive call followed by five to 23 notes similar to the advertisement call, probably a strategy to partition the attractive and aggressive functions in different notes on the same call. We suggest that the mixed calls of H. werneri could be a graded aggressive call system, already found in other anurans, which allows males to gradually reduce the number of attractive elements while increasing the aggressiveness of the call.